Psychometric Characteristics of a Saudi Version of Wechsler Intelligence Scale for Preschool and Young Children - Ejbara, Mohammad Adnan (Dirasat: Educational Sciences, 2024)
Objectives: This study aimed to verify the psychometric characteristics of the Saudi version of the WPPSI III for preschool and young children. Methods: The descriptive method was used to achieve the study's objectives; the study population consisted of all children in the Jeddah Educational District from 4 to 7.3 years old. The study sample consisted of (788) candidates between the years 2018- 2022 who were selected through Stratified sampling. The study tool used the WPPSI III, which consists of (11) subtests (5 performance, 6 verbal). Results: Construct validity of the scale was verified through confirmatory and exploratory factor analysis. As for the discriminant validity, results showed statistically significant differences between normal children and special education groups, in favor of normal children, according to the age group, and in favor of the oldest age. Correlative validity was also verified, as the correlation coefficient between the Wechsler-Binet intelligence scale, the Saudi version reached (0.81) and the Goodenough Saudi version test (0.71). There was also evidence of the scale's reliability using the split-half, test-retest, and internal consistency methods. The initial standard of the scale was also derived by converting the raw score into a scaled score and an IQ with a mean of 100 and a deviation of 15. Conclusions: using the WPPSI in evaluating preschool and young children's stages.